2013
DOI: 10.3329/bjp.v8i2.13797
|View full text |Cite
|
Sign up to set email alerts
|

Eriocalyxin B inhibits proliferation and induces apoptosis through downregulation of Bcl-2 and activation of caspase-3 in human bladder cancer cells

Abstract: Eriocalyxin B inhibits proliferation and induces apoptosis through down -regulation of Bcl-2 and activation of caspase-3 in human bladder cancer cells Bangladesh Journal of Pharmacology Research Article IntroductionNatural products provide many promising sources of potential anti-cancer agents and several lead structures in the past decades, which were originally isolated from plants such as paclitaxel, camptothecin, vinca alkaloids, and etoposide have potential application in cancer chemotherapy, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Eriocalyxin B has been documented to possess a variety of pharmacological activities, which has the effects of antiinflammatory, antiproliferative, anti-angiogenic, and the most common activity is anti-cancer [29,35,36]. In this work, we reported that eriocalyxin B is capable of inhibiting adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Eriocalyxin B has been documented to possess a variety of pharmacological activities, which has the effects of antiinflammatory, antiproliferative, anti-angiogenic, and the most common activity is anti-cancer [29,35,36]. In this work, we reported that eriocalyxin B is capable of inhibiting adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 70%
“…Many studies show that MCE is a prerequisite for differentiation of 3T3-L1 preadipocytes into adipocytes. A study demonstrated that Eriocalyxin B markedly arrested cell cycle at G2/M phase in a dosedependent manner [29]. CDKs are serine/threonine kinases that control cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of bcl2 leads to the release of cytochrome c from mitochondria to the cytosol, resulting in cell death. Eriocalyxin B inhibits the proliferation and induces apoptosis through downregulation of bcl2 (Rasul et al, 2013). Studies examined that the cellular levels of cytochrome c, caspase 3, PARP, p53, bax, bcl2 and β-actin expression after baicalein treatment.…”
Section: Discussionmentioning
confidence: 99%